Samcio181
Rozwiązane

oblicz wartość danego wyrażenia:
a) [(x/y)³:(x/y)⁻²]²*(x/y)⁻⁷= ,dla x=1/2 i y=(1/2)⁻¹

b)[(1/8a):(1/4a²)²]*(a*1/2)⁴= ,dla a=(-2)⁻¹

proszę o obliczenia :D



Odpowiedź :

a)[(x/y)³:(x/y)⁻²]²*(x/y)⁻⁷= ,dla x=½ i y=(½)⁻¹
Najpierw uprościmy wyrażenie : [(x/y)³:(x/y)⁻²]²*(x/y)⁻⁷ czyli:
[(x/y)³:(x/y)⁻²]²*(x/y)⁻⁷ = (x/y)⁶:(x/y)⁻⁴*(x/y)⁻⁷(x/y)⁶⁺⁴⁻⁷=(x/y)³
i:
y=(½)⁻¹=2
(x/y)³=(½/2)³=(½:2)³=(½*½)³=(¼)³=1/64

b)[(⅛a):(¼a²)²]*(a*½)⁴= ,dla a=(-2)⁻¹
również upraszczamy:
[(⅛a):(¼a²)²]*(a*½)⁴= [(⅛a):(1/16a⁴)]*(1/16a⁴)=2a⁻³*1/16a⁴=⅛a
a=(-2)-1=-½
⅛*(-½)=-1/16

:)